Exploring the Impact of Teaching Strategies on Students' Critical Thinking Skills in Chemistry - Casmini, Ni Luh; Redhana, I Wayan; Suma, I Ketut (Universitas Pendidikan Ganesha, 2024)
The low level of students' critical thinking skills in learning chemistry is still a challenge at the high school level. This condition is caused by the lack of application of learning models that can encourage students to think analytically and reflectively. This study aims to analyze the results of the analysis of students' critical thinking skills through the application of discovery learning models in chemistry subjects in class XI SMA. This research used qualitative research method with descriptive analysis approach. The research subjects included chemistry teachers and students. Data collection was done through observation, interview, and document analysis. Data analysis techniques used triangulation, member check, audit trail, and credibility checking to ensure the validity of the findings. The results showed differences in the level of students' critical thinking skills during the learning process with the discovery model. Some critical thinking indicators, such as the ability to analyze information and provide logical arguments, have not been applied optimally by students. Differences in classroom interactions also affected students' learning outcomes. Teacher 1 applies multi-directional interactions that encourage active discussions, while Teacher 2 tends to use unidirectional interactions that limit students' participation. Teachers' teaching skills play an important role in facilitating the development of students' critical thinking skills. The conclusion of this study shows that the discovery learning model can improve students' critical thinking skills if supported by effective interactions and adequate teacher teaching skills.